2021
DOI: 10.3390/antibiotics10091123
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-Counter Sale of Antibiotics in India: A Qualitative Study of Providers’ Perspectives across Two States

Abstract: India has one of the highest rates of antimicrobial resistance (AMR) worldwide. Despite being prescription drugs, antibiotics are commonly available over-the-counter (OTC) at retail pharmacies. We aimed to gain insight into the OTC sale of antibiotics at retail pharmacies and to elucidate its underlying drivers. We conducted face-to-face, in-depth interviews using convenience sampling with 22 pharmacists and 14 informal dispensers from 36 retail pharmacies across two Indian states (Haryana and Telangana). Them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…The study illustrated a possible mechanism of doxycycline-selected resistance and co-resistance in V. cholerae and warranted strict restrictions on the indiscriminate use of antibiotics. Another facet is the limitation of unrestricted sale of these antibiotics without prescription especially in developing countries like India, one of the largest antibiotic consumer ( Kotwani et al, 2021 ). So, the controlled usage of these repurposed antibiotics will be jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…The study illustrated a possible mechanism of doxycycline-selected resistance and co-resistance in V. cholerae and warranted strict restrictions on the indiscriminate use of antibiotics. Another facet is the limitation of unrestricted sale of these antibiotics without prescription especially in developing countries like India, one of the largest antibiotic consumer ( Kotwani et al, 2021 ). So, the controlled usage of these repurposed antibiotics will be jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study published in September 202110 looking at antibiotic overuse in two Indian states (Haryana in the north and Telangana in the south) found that in 36 retail pharmacies, antibiotics from the WHO’s access and watch groups were often dispensed for fever, cough, cold, and acute diarrhoea. They cited profit motives, as well as patients buying antibiotics because they can’t see a doctor (because of access issues or cost), as reasons behind the overuse.…”
Section: Progressmentioning
confidence: 99%
“…One way to potentially change individual ethical behaviour is through targeted prescriber and general public education campaigns so that doctors and the general public are continuously made aware of the deleterious effect and risk associated with the irrational use of antibiotics to treat unconfirmed bacterial infections [ 11 ]. Ethically speaking, however, one of the possible ethical consequences of such policy implementations may be a reduction in the standard of living of vendors via the profits made by selling antibiotics [ 12 , 13 ]. Another ethical problem is that blocking access to antibiotics may unfairly target lower income groups who cannot afford to pay for a visit to a doctor, or a diagnostic test, on top of the cost of antibiotic treatment.…”
Section: Ethical Perspectives On the Overuse Use Of Antibioticsmentioning
confidence: 99%